The Effectiveness of the DASHAT BINTANG Program in Improving the Knowledge of Mothers of Toddlers Regarding Stunting Prevention in Sedayu Village - Adinda Restu Pramesty; Chatila Maharani; Sheollum Najwa Zeymuna; Laurent Tira; Isna Anggita; Haickal Adyanaka Grivaldi Ramadhan; Salma Rif’atun Nisa; Naya Aulya Putri; Nadin Nadia Khoirunnisa; Naisya Ridya Niar Aulia; Sariyun Sariyun (Hippocratica : Journal of Modern Medicine and Healthcare Practice, 2026)
Stunting remains a critical public health challenge requiring community-based interventions that strengthen maternal knowledge and nutritional practices. This study aimed to evaluate the effectiveness of the DASHAT BINTANG Program in improving mothers’ knowledge regarding stunting prevention in Sedayu Village. An empirical pre-experimental study with a one-group pretest-posttest design was conducted involving 10 mothers of toddlers selected through total sampling. Data were collected using structured knowledge assessments before and after an intervention consisting of nutritional education, child growth monitoring guidance, balanced feeding practices based on the Isi Piringku guideline, and a local food processing demonstration. Data were analyzed using the Wilcoxon Signed-Rank Test. The results showed an increase in the mean knowledge score from 96 to 116 after the intervention, with a statistically significant difference between pretest and posttest scores (p = 0.017). The program also improved mothers’ understanding and practical awareness regarding the utilization of local food for toddler nutrition. The DASHAT BINTANG Program represents an effective community-based strategy for strengthening maternal capacity in supporting stunting prevention through integrated education and practical empowerment.